Μ-Opioid receptor activation modulates CA3-to-CA1 gamma oscillation phase-coupling. (June 2019) - Zhang, Yujiao; Ahmed, Sanya; Neagu, Georgiana; Wang, Yali; Li, Zhenyi; Wen, Jianbin; Liu, Chunjie; Vreugdenhil, Martin
Highlights: CA3 gamma oscillation (γ) drives CA1 gamma and suppresses CA1 intrinsic fast γ. μ-opioid receptor (MOR) activation reduces γ frequency in CA3 and CA1. MOR activation in CA1 phase-uncouples CA1 γ from CA3 γ. Uncoupling is not due to CA3 γ deceleration by MOR activation. Abstract: In the intact brain, hippocampal area CA1 alternates between low-frequency gamma oscillations (γ), phase-locked to low-frequency γ in CA3, and high-frequency γ, phase-locked to γ in the medial entorhinal cortex. In hippocampal slices, γ in CA1 is phase-locked to CA3 low-frequency γ. However, when Schaffer collaterals are cut, CA1 can generate its own high-frequency γ. Here we test whether (un)coupling of CA1 γ from CA3 γ can be caused by μ-opioid receptor (MOR) modulation. In CA1 minislices isolated from rat ventral hippocampus slices, MOR activation by DAMGO reduced the dominant frequency of intrinsic fast γ, induced by carbachol. In intact slices, DAMGO strongly reduced the dominant frequency of CA3 slow γ, but did not affect γ power consistently. DAMGO suppressed the phase coupling of CA1 γ to CA3 slow γ and increased the power of CA1 intrinsic fast γ, but not in the presence of the MOR antagonist CTAP. The benzodiazepine zolpidem and local application of DAMGO to CA3 both mimicked the reduction in dominant frequency of CA3 slow γ, but did not reduce the phase coupling. Local application of DAMGO to CA1 reduced phase coupling. These results suggest that MOR-expressing CA1 interneurons, feed-forwardly activated by Schaffer collaterals, are responsible for the phase coupling between CA3 γ and CA1 γ. Modulating their activity may switch the CA1 network between low-frequency γ and high-frequency γ, controlling the information flow between CA1 and CA3 or medial entorhinal cortex respectively.